2016
DOI: 10.1017/s2398772300002890
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Symposium on the Many Lives and Legacies of Sykes-Picot

Antony T. Anghie

Abstract: Although their motivations varied, many senior British officials who were expert in imperial and Middle-Eastern matters condemned the Sykes-Picot treaty as a mistake almost as soon as it was signed. T.E. Lawrence wanted the British government to repudiate it and was assured by Gilbert Clayton, the head of the Arab Bureau in Cairo, in a letter he wrote to Lawrence in 1917, that “‘It is in fact dead and, if we wait quietly, this fact will soon be realized’.” Lord Curzon denounced the treaty as “not only obsolete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The agreement, leaked by newly empowered Bolsheviks in Russia in 1917, indicated that the UK government intended to renege on its promises it made to Arab nations. While the legacy of Sykes-Picot is contested, the secret agreement is characterized as a critical part of Middle East history (Anghie, 2016). Since truly secret agreements are by their nature difficult to quantify, it is hard to know how many of them exist.…”
Section: Negotiating In Secretmentioning
confidence: 99%
“…The agreement, leaked by newly empowered Bolsheviks in Russia in 1917, indicated that the UK government intended to renege on its promises it made to Arab nations. While the legacy of Sykes-Picot is contested, the secret agreement is characterized as a critical part of Middle East history (Anghie, 2016). Since truly secret agreements are by their nature difficult to quantify, it is hard to know how many of them exist.…”
Section: Negotiating In Secretmentioning
confidence: 99%